The current state of the forensic psychiatric examination in Russia - Шунк, Вікторія Едуардівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article discusses the current state of the forensic psychiatric examination in Russia, based on a comprehensive study of the historical and legal laws and their application. Outlines the legal status of persons in respect of which an examination.